Influence of Financial Inclusion on Informal Sector Small and Medium Scale Enterprises’ Employment in Sub-Saharan Africa: Moderating Role of Mobile Money - Enoch Kojo Ackom; Evans O.N.D. Ocansey (European Scientific Journal, ESJ, 2025)
The informal sector remains a dominant force in Sub-Saharan Africa (SSA), with small and medium-sized enterprises (SMEs) serving as critical engines of employment and livelihood. However, limited access to financial services continues to constrain the growth and sustainability of these businesses. This study investigates the impact of financial inclusion on employment outcomes among informal SMEs in SSA, with a particular focus on the moderating role of mobile money. The study analyzed a panel data from 38 SSA countries between 2000 and 2023 with a two-step System Generalized Method of Moments (GMM). Findings reveal that while financial inclusion has a weak positive effect on employment, mobile money alone also shows a modest direct effect. However, the interaction between financial inclusion and mobile money is negative and statistically significant, suggesting that mobile money may dilute the employment-enhancing impact of broader financial inclusion when both coexist. The results also confirm strong employment persistence and limited influence from macroeconomic control variables. The study implies that policymakers should treat financial inclusion and mobile money not as interchangeable tools but as complementary elements that require careful coordination. Additionally, the findings offer new directions for accounting research, especially in the context of informal financial data and reporting practices. Future work should consider firm-level data, gender-disaggregated analysis, and evolving financial technologies to better understand SME dynamics in Africa’s informal economy.